Perlindungan Hukum Terhadap Hak Atas Tanah Bersertifikat - Ester Senov Fitriani Simanjuntak; Ikhsanul Fadly Butar Butar; Lina Adinda Krisma Suci Hutabarat; Muhammad Rifai; Ramsul Nababan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze legal protection for holders of certified land rights. The research method used is the library study research method by utilizing sources related to the research title through books, journals, notes, previous research, and the like. The research results show factors that cause double certificates, such as inaccuracy and carelessness in the process of issuing certificates by the National Land Agency. The emergence of multiple certificates creates legal uncertainty for the owner and has the potential to cause disputes and losses for both parties. The legal protection obtained by land rights owners who are disadvantaged due to double certificates in the form of cancellation and revocation of related documents which are considered detrimental. From this research, it can be concluded that legal protection for certified land rights holders is important to ensure legal certainty and prevent the occurrence of disputes that harm the owners of land rights